Analisis Komunikasi Interpersonal Anggota Komunitas Orca Di Media Sosial Discord - Nugroho, Pramudya Wahyu; Rina, Nofha (eProceedings of Management, 2024)
Thel development ofl information andl communication ltechnology, especially the internet, hasl had al significantimpactl on thel way humans interact andl form communities. Thel emergence of virtual communities has become aninteresting phenomenon in the current digital era. To communicate with each other in a virtual community, the VirtualCommunity uses various media, one of which is Discord, which isl an applicationl that canl be usedl tocommunicatel together andl can alsol be usedl to createl a lcommunity, onel of whichl is thel Orca lcommunity. Inthel Orca lcommunity, communicationl is carried out onlinel and therel are membersl from variousl regions andlvarious lages. Thisl research wasl conducted tol analyze thel effectiveness ofl interpersonal communication betweenmembers of the Orca community on Discord social media. Thisl research usesl qualitative researchl methods, thenlinterviews andl data lcollection. Researchersl obtained research resultsl from thel existence ofl openness, lempathy,lfeeling, positivity, lsupport, andl equality so thatl communication canl be carried out effectivelyl to increasel thesensel of kinshipl within thel Orca lcommunity. Keywords-interpersonal communication, virtual community, effectiveness of interpersonal communication, discordsocial media.